Postnatal Vitamin D Intake Modulates Hippocampal Learning and Memory in Adult Mice - Liang, Qiujuan; Cai, Chunhui; Duan, Dongxia; Hu, Xinyu; Hua, Wanhao; Jiang, Peicheng; Zhang, Liu; Xu, Jun; Gao, Zhengliang (Frontiers in Neuroscience, 2018)
Vitamin D (VD) is a neuroactive steroid crucial for brain development, function and homeostasis. Its deficiency is associated with numerous brain conditions. As such, VD and its variants are routinely taken by a broad of groups with/without known VD deficiency. In contrast, the harmful effects of VD overdose have been poorly studied. Similarly, the developmental stage-specific VD deficiency and overdose have been rarely explored. In the present work, we showed that postnatal VD supplementation enhanced the motor function transiently in the young adult, but not in the older one. Postnatal VD intake abnormality did not impact the anxiety and depressive behavior but was detrimental to spatial learning and hippocampus-dependent memory. At the molecular level we failed to observe an obvious and constant change with the neural development and activity-related genes examined. However disrupted developmental expression dynamics were observed for most of the genes, suggesting that the altered neural development dynamics and therefore aberrant adult plasticity might underlie the functional deficits. Our work highlights the essence of VD homeostasis in neural development and adult brain function. Further studies are needed to determine the short- and long-term effects VD intake status may have on brain development, homeostasis and diseases.